The embodiment of Muslim intention elements in buying halal food products: a literature review - Nur Wiyono, Sulistyodewi; Deliana, Yosini; Wulandari, Eliana; Kamarulzaman, Nitty Hirawaty (Multidisciplinary Digital Publishing Institute, 2022)
Countries with mostly Muslim populations should have more halal-certified products for domestic consumption. In Indonesia, only a few food products are halal-certified, whereas many products are not certified, but are still consumed by Muslims. Therefore, this study aims to reveal the manifestations of consumer intentions in buying halal food products, and how this intention affects Muslim consumers in purchasing halal food products. This is a semi-systematic literature study that identifies and analyzes articles on a highly scientific database spanning a decade. VOSviewer is used to visualize the development of scientific topics that have been published through keywords. These findings provide in-depth insight into the intentions of Muslims in buying halal food products. This study can also assist the study of halal food products that analyze the factors of intention and contribute to the sustainable buying behavior of consumers in the future.